Edições fac-similar e semidiplomática do livro de registro da correspondência official da Presidência da província com a repartição eclesiástica : 1887 – 1890. aspectos ortográficos - Façanha, Juliana Lima (2012)
This research, guided by philological science, aims to present the issues and facsimile semi-diplomatic of the selected document in the Public Archives of the State of Mato Grosso titled "Livro de registro da correspondencia official da Presidencia da provinica com a repartiçaõ ecclesiastica: 1887-1889", followed by some comments from paleographic nature through analysis of the calligraphic types and paleographic guide proposed by Cambraia (2005, p. 24), analysis of the codex support material, which is the science correspondent to codicology and description of spelling occurrences present in this manuscript. It is also a study of the historical context of relations between the state and the Catholic Church, in view of the manuscript being exploited, especially the economic, financial and political relations beyond the transition phase from Empire to Republic in Brazil. This research is part of the Post-Graduation Program in Linguistic Studies at the Languages Institute - UFMT, and is linked to the "Study of the Portuguese language in manuscripts produced in Mato Grosso since the eighteenth century" research project, at Meel/UFMT, and the project ́s theme: "For the history of Brazilian Portuguese - PHPB.